Strengthening Independent Character Education of Santri through Pesantrenpreneur in Islamic Boarding School - Mufattakhatin, Erina Nur; Junaedi, Mahfud; Lutfiyah, Lutfiyah (Southeast Asian Journal of Islamic Education, 2025)
This research aims to analyze the process and the implications of strengthening the independence character education through pesantrenpreneur at the Fadhlul Fadhlan Islamic Boarding School in Semarang. This study used a qualitative approach with a phenomenological approach. The subjects of this study were a caregiver, three administrators, and five santri who participate in pesantrenpreneur. The data collection techniques used observation, interviews, and documentation, while the data analysis techniques used qualitative methods of the Creswell model. The study results show that the process of strengthening independence character education through pesantrenpreneur at the Fadhlul Fadhlan Islamic Boarding School is carried out continuously through three stages, namely providing understanding (moral knowing), instilling awareness (moral feeling), and providing examples or role models (moral action). Strengthening independence character education through pesantrenpreneur has given positive implications for the independence of santri who are increasingly strong, namely having a desire to develop, showing their activeness in taking the initiative and being able to overcome problems, being more confident and able to carry out tasks on their own, and starting to be aware of responsibility. This change is reflected in the emotional independence, values​​, and behavior of santri in everyday life, so that it can be used as provisions for future life. The importance of this research is relevant in an effort to answer the challenges of 21st-century education, where the educational process in Islamic boarding schools is required not only to be able to produce santri who are intelligent in religious knowledge, but also independent in personality.